Development of piezoelectric micro-energy harvesting system using voltage doubler - Mostafa, Mohammad Golam; Motakabber, S. M. A.; Ibrahimy, Muhammad Ibn; Rahman, Towfikur (Asian Research Publishing Network (ARPN), 2016)
Nowadays renewable energy and its harvesting are attractive, because this energy is free which leads to reduce energy cost. One of the common energy harvesting techniques is a piezoelectric based system. But the output of a piezoelectric transducer which is an AC signal and its obtained voltage from the transducers is usually very small quantity. Therefore, convertion of this low voltage by rectifier is not suitable because rectifier offers a nonlinear load for energy harvesting system. A micro-energy harvesting interface circuit has been developed to improve the performance. This design is a modified model of buck boost converter which at first doubles the input voltage and then operates as a buck boost converter. A diode and a single capacitor have been used in this design instead of bridge rectifier which overcomes the diode conduction losses. It rated output voltage of 3.4V DC across a load 1kΩ while the input voltage of the circuit from the piezoelectric transducer is 0.54V AC in amplitude. The circuit has been simulated using PSpice (V16.5) electronic circuit simulation software. It is resulting that the maximum output power across the load is 57mW which is better compared to other designs.